NY Bootes: An Active Deep and Low-mass-ratio Contact Binary with a Cool Companion in a Hierarchical Triple System - Fangbin Meng; Liying Zhu; Shengbang Qian; Nianping Liu; Linjia Li; Azizbek Matekov (The Astrophysical Journal, 2023)
The first detailed photometric and spectroscopic study of G-type short-period binary NY Boo is presented. The radial velocity curve was obtained by the cross-correlation function (CCF) method based on LAMOST and SDSS spectra, which derived its mass ratio as q = 0.139(1/7.2). The CCF profiles of the SDSS spectra clearly show the existence of a cool third component, which is supported by the results of the orbital period investigation. The period study based on the O-C analysis indicates that besides a long-term decrease, the orbital period has a periodic oscillation due to the light-travel time effect caused by a third body. When the third light contribution is consistent with the CCF results, the orbit of the third body and the inner pair are non-coplanar with m _3 = 0.31 M _⊙ . Combining with the TESS light curves, it is found that the target is a deep and low-mass-ratio contact binary (DLMRCB) with a fill-out factor of f = 73%. The notable asymmetry in light curves was detected and explained by the spot model very well. The spectroscopic profiles, the cyclic variation in the O-C diagram, and the radial velocity curve and light-curve solutions all suggest that NY Boo is a hierarchical triple system with a cool tertiary component orbiting around an active DLMRCB. With the orbital period shrinking, the binary may eventually merge. The period of NY Boo decreases faster than other shrinking DLMRCB, together with active inner pair and non-coplanar tertiary component, making NY Boo an important target for studying the late evolution of binaries.